Norepinephrine-Induced Stimulation of Kir4.1/Kir5.1 Is Required for the Activation of NaCl Transporter in Distal Convoluted Tubule. Issue 1 (January 2019) - Duan, Xin-Peng; Gu, Li; Xiao, Yu; Gao, Zhong-Xiuzi; Wu, Peng; Zhang, Yun-Hong; Meng, Xin-Xin; Wang, Jun-Lin; Zhang, Dan-Dan; Lin, Dao-Hong; Wang, Wen-Hui; Gu, Ruimin
Abstract : The stimulation of β–adrenergic receptor increases thiazide-sensitive NaCl cotransporter (NCC), an effect contributing to salt-sensitive hypertension by sympathetic stimulation. We now test whether the stimulation of β–adrenergic receptor-induced activation of NCC is achieved through activating basolateral Kir4.1 in the distal convoluted tubule (DCT). Application of norepinephrine increased the basolateral 40 pS K + channel (Kir4.1/Kir5.1 heterotetramer) in the DCT. The stimulatory effect of norepinephrine on the K + channel was mimicked by cAMP analogue but abolished by inhibiting PKA (protein kinase A). Also, the effect of norepinephrine on the K + channel in the DCT was recapitulated by isoproterenol but not by α–adrenergic agonist and blocked by propranolol, suggesting that norepinephrine effect on the K + channel was mediated by β–adrenergic receptor. The whole-cell recording shows that norepinephrine and isoproterenol increased DCT K + currents and shifted the K + current ( I K ) reversal potential to negative range (hyperpolarization). Continuous norepinephrine perfusion (7 days) increased DCT K + currents, hyperpolarized I K reversal potential, and increased the expression of total NCC/phosphorylated NCC, but it had no significant effect on the expression of NKCC2 (type 2 Na-Cl-K cotransporter) and ENaC-α (epithelial Na channel-α subunit). Renal clearance study demonstrated that norepinephrine perfusion augmented thiazide-induced urinary Na + excretion only in wild-type but not in kidney-specific Kir4.1 knockout mice, suggesting that Kir4.1 is required for mediating the effect of norepinephrine on NCC. However, norepinephrine perfusion did not affect urinary K + excretion. We conclude that the stimulation of β–adrenergic receptor activates the basolateral Kir4.1 in the DCT and that the activation of Kir4.1 is required for norepinephrine-induced stimulation of NCC. Abstract : Supplemental Digital Content is available in the text.